Introduction: The internationalisation of the innovation process. - Michie, J (Carfax Publishing Ltd., 1998)
The international economics of business and management has focused - both in the academic literature and in corporate and public policy discussions - increasingly on issues of globalisation, innovation and 'competitiveness'. These issues, and in particular their interrelation, are analysed in detail in this Special Issue of the International Journal of the Economics of Business. This opening article aims to set the scene by considering how the rather distinct literatures around the above three topics can best be drawn upon in order to focus on what implications the new global economic environment has for the economics of business and public policy.